Optimal exercise interventions for enhancing cognitive function in older adults: a network meta-analysis - Han Han; Jinhao Zhang; Fan Zhang; Fanghui Li; Zhijian Wu (Frontiers in Aging Neuroscience)
Background: Cognitive decline poses a significant challenge to healthy aging. While exercise is widely recognized for its cognitive benefits, the comparative efficacy of different exercise modalities and optimal intervention protocols for specific cognitive domains in older adults remains unclear.Objective: This network meta-analysis aimed to systematically compare the effects of five exercise modalities—resistance training, aerobic exercise, mind-body exercise, multicomponent exercise, and high-intensity interval training (HIIT)—on global cognitive function and major cognitive domains in cognitively healthy older adults, and to identify optimal intervention protocols and population subgroups most likely to benefit.Methods: A total of 58 randomized controlled trials (RCTs) were included, encompassing 4,349 healthy older adults from diverse geographical regions. Comprehensive searches were conducted in major electronic databases for RCTs evaluating exercise interventions on cognitive outcomes in adults aged 60 years and older. A network meta-analysis assessed the relative effects of each exercise modality on global cognition, executive function (including inhibitory control, task-switching ability, and working memory), and memory function. Subgroup analyses were performed based on intervention frequency, duration, participant age, and geographic region.Results: Resistance training demonstrated the greatest improvement in global cognitive function (SMD = 0.55) and inhibitory control (SMD = 0.31, SUCRA = 82.1%), particularly with twice-weekly sessions of 45 min over 12 weeks. Mind-body exercise was most effective for executive function, especially task-switching ability (SMD = −0.58, SUCRA = 85.1%) and working memory (SMD = 2.45), with high-frequency, moderate-duration protocols yielding optimal results. Aerobic exercise was the most effective modality for enhancing memory function (SMD = 0.42). The largest cognitive benefits were observed in participants aged 65–75 years and in studies conducted in Asia.Conclusion: Different exercise modalities provide domain-specific cognitive benefits in healthy older adults. Personalized exercise prescriptions—emphasizing resistance training for global cognition, mind-body exercise for executive function, and aerobic exercise for memory—should be considered in clinical and public health settings. These findings support the integration of structured exercise interventions into aging and dementia prevention strategies, with particular attention to optimal protocol design and population targeting.